Learning Motivation as Mediator of Associations Between Students' Interest, Positive Learning Environment, and Vocabulary Knowledge - Riska Alifiah Zalsabila; Muhammad Tahir; Muhalim Muhalim (PT. Global Research Collaboration, 2026)
This study explored the relationships among students' interest, positive learning environment (PLE), motivation, and vocabulary knowledge among Indonesian EFL learners. Data were obtained using a cross-sectional explanatory sequential mixed-methods design using convenience sampling from 236 eleventh-grade students of three public senior high schools in Takalar Regency, Indonesia, and were followed by interviews with 14 purposively selected students. Quantitative data were examined with Structural Equation Modelling (SEM), whereas qualitative interview data were assessed via thematic analysis. The findings demonstrated that motivation was strongly correlated with students' interest and a supportive learning environment. While there was no statistically significant correlation between students' interest and vocabulary knowledge, motivation and a supportive learning environment were strongly linked to vocabulary knowledge. Significant indirect relationships between students' interest and vocabulary knowledge (β =.140, p <.001) and between a positive learning environment and vocabulary knowledge (β =.093, p =.002) were found by mediation analysis. The results indicate that among Indonesian EFL learners, motivation plays a role in explaining the relationships between students' interest, a supportive learning environment, and vocabulary knowledge.